Interpretation: The Infinite Controversy - S. Sultan, Sabbar (Penerbit Universiti Sains Malaysia (USM Press), 2010)
The following is an attempt to view and perceive the problematic act of interpretation, including its nature, its endless controversies, its horizons and its limitations. The paper is comprised of two sections. The first is an introduction covering the various aspects of the interpretive act. It also deals with the vast potentialities opened up by interpretation. The second section shows some of the limitations of interpretation, as seen in the different interpretations of Conrad's Heart of Darkness and Shakespeare's Hamlet. The approach used throughout is ambivalent in that it stresses the merits and drawbacks of interpretation in reading and understanding texts.